Profit Efficiency in Lithuanian Credit Unions – a DEA Approach - Kėdaitis, Vytautas; Baležentis, Tomas; Valkauskas, Romualdas; Mikučionytė, Žymantė (Ekonomika, 2018)
The paper proceeds by discussing the different definitions of credit unions. The research focuses on the efficiency of the credit unions in Lithuania. Indeed, efficiency is the degree to which the rational use of limited economic resources is ensured. More specifically, we focus on the economic efficiency of the credit unions. The methodology that is followed in the paper comprises the measures of cost and profit efficiency. Further on, profit efficiency is defined in terms of both standard profit efficiency and alternate profit efficiency. The measures of efficiency are implemented via the data envelopment analysis (DEA). The frontier model comprises the two outputs and the three inputs. The calculations confirm the operationality of the proposed methodology for rating credit unions according to the efficiency of their activity.